Vernacularisation of Acehnese Literature and Religious Works in the 19th Century AD: A Philological Approach - Erawadi, Erawadi (Journal of Al-Tamaddun, 2024)
This article discusses the development of local translation and the transformation of literature and religious works into the Acehnese language. Even though this literature and religious works had appeared since the 17th century AD, significant progress only found momentum in the 19th century. Employing a philological approach, this study analyses written manuscripts using descriptive and analytic methods to explore the vernacularisation of Acehnese literary and religious works. The research reveals that in the 19th century, there was a development of literary and religious writings in the Acehnese language, along with the decline in the role of Malay as a regional language in Southeast Asia. This shift is evidenced by a number of local Acehnese literary works written in the Jawi script (Arabic-Acehnese). On the one hand, this transition reflects the waning influence of the Malay language in Aceh. Still, on the other hand, they have become the momentum for translating and transforming religious values ​​for the people of Aceh.